2018
DOI: 10.1111/jmwh.12701
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes in the Birth Center Setting: A Systematic Review

Abstract: There are substantial flaws in the literature concerning the effect of birth center care on neonatal outcomes. More research is needed on subgroups at risk of poor outcomes in the birth center environment. To expedite research, consistent use of national and international definitions of perinatal and neonatal mortality within data registries and greater detail on adverse outcomes would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
10
0
3
Order By: Relevance
“…36,37 Variables that reliably and validly indicate neonatal health and transition to extrauterine life are currently lacking. 38 Development of such variables is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Variables that reliably and validly indicate neonatal health and transition to extrauterine life are currently lacking. 38 Development of such variables is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of freestanding birth centers have consistently demonstrated safe, high‐quality care with fewer medical interventions during labor than usual care, while achieving lower cesarean birth rates . Neonatal outcomes have been similar to those of lower‐risk mothers in usual care …”
Section: Introductionmentioning
confidence: 95%
“…Guidelines for obesity that are not data based limit access to midwifery care for women with obesity from vulnerable circumstances, care that has been shown safe, effective, and cost-effective. [11][12][13][14][15] Additionally, overapplication of treatments meant to avoid obesity-related risk may unnecessarily increase risk for iatrogenic complications such as uterine hyperstimulation during augmentation of labor with oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…The perinatal outcomes of women with obesity receiving antenatal care from physicians and giving birth in hospitals have been documented and analyzed for 30 years. [5][6][7][8] Multiple studies have reported excellent perinatal outcomes for women receiving antenatal care and giving birth in freestanding birth centers; [11][12][13][14][15] however, the outcomes specific to women with obesity receiving care based on midwifery models and giving birth in US freestanding birth centers have not been separately examined. In this study, we compared maternal and neonatal outcomes between woman with normal weights and those with obesity admitted to US birth centers.…”
Section: Introductionmentioning
confidence: 99%